Evaluation of the Implementation of Clinical Pharmacy Services at Kupang City Pharmacy Based on PERMENKES RI Number 73 of 2016 - Patty, Yohana Febriani Putri Peu; Parwati, Dian (Journal of Pharmaceutical and Sciences, 2025)
Clinical pharmacy services in pharmacies are one of the responsibilities that pharmacists must perform. Some of the clinical pharmacy service activities contained in the applicable pharmaceutical service standards are prescription service assessment, dispensing, Drug Information Services (PIO), Counseling, Drug Therapy Monitoring (PTO), Monitoring Drug Side Effects (MESO). The purpose of this study was to determine the suitability of the implementation of clinical pharmacy services in the Kupang City Pharmacy area against the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016. This research method was carried out descriptively with a cross-sectional method. Sample selection was carried out by purposive sampling involving 10 pharmacies that met the inclusion criteria. Data collection was carried out using the interview method using an interview guideline sheet. The results showed that the implementation of clinical pharmacy services in 10 pharmacies in the aspect of reviewing prescription services was 100% (in accordance with the SPKA), the dispensing aspect was 100% (in accordance with the SPKA), the Drug Information Service (PIO) aspect was 100% (in accordance with the SPKA), the counseling aspect was 60% (not in accordance with SPKA). The home pharmacy care aspect, the Drug Therapy Monitoring (PTO) aspect and the Monitoring of Drug Side Effects (MESO) aspect was 100% not implemented by all pharmacy. Conclusion pharmacies in Kupang City have not fully implemented clinical pharmacy services based on the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016.